Pharmacokinetics and Biodistribution of Paclitaxel-loaded Microspheres - Yan, F.; Tang, S.; Fu, Q. (Arzneimittelforschung, 2012)
Paclitaxel(PTX)-loaded microspheres composed of poly(D,L-lactide-co-glycolide) (PLGA) were prepared by an O/W emulsion solvent evaporation method. This study was designed to investigate the preparation, in vitro release, in vivo pharmacokinetics and tissue distribution of a PTX-loaded microspheres system. Microspheres are characterized according to drug loading, size and shape. With a dynamic light scattering sizer and a transmission electron microscopy, it is shown that the PTX-loaded microspheres had a mean size of approximately 10.24 µm with narrow size distribution and a spherical shape. The in vitro release profiles indicate that the release of PTX from the microspheres exhibit a sustained release behavior. A similar phenomenon is observed in a pharmacokinetic study in rats, in which AUC of the microspheres formulation were 3.7-fold higher than that of PTX injection. The biodistribution study in mice showed that the PTX-loaded microspheres not only decreased drug uptake by liver, but also increased distribution of drug in lung. These results suggest that PTX-loaded microspheres may efficiently load, protect and retain PTX in both in vitro and in vivo environments, and could be a useful drug carrier for i. v. administration of PTX.
Keywords: paclitaxel; microspheres; pharmacokinetics; biodistribution